Effect of Newtonian Heating on the Mixed Convection Boundary Layer Flow of Eyring-Powell Fluid Across a Nonlinearly Stretching Sheet - Al-Sharifi, H. A. M.; Abdul Rahman, Mohd Kasim; Mohd Zuki, Salleh (Medwell Journals, 2016)
The problem on mixed convection boundary layer flow of Eyring-Powell fluid across a nonlinear stretching sheet together with the effect of Newtonian heating is examined. The governing equations are transformed into a system of ordinary differential equations using a similarity transformation and then solved by employing the Range-Kutta method. The effects of the Prandtl number, pr fluid ε parameter conjugate r parameter for Newtonian heating γ and mixed convection parameter λ on the velocity and temperature profiles are computed and discussed. Increasing on the values of parameters g, γ and λ resulted in an increase in the velocity while increasing on the values of caused in decreasing on the values of fluid velocity. In addition, temperature of fluid decreased with an increasing in the value of parameters Pr, ε and λ but increases with increasing γ.